Regulation of Agricultural and Livestock Relations in the Legal System of the Tangut State (Si Sya) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article analyzes the economic foundations of the legal system of the Tangut state (Si Sya) during the 11th-13th centuries, focusing specifically on the legal norms regulating agriculture and livestock. The study is based on the fundamental monograph by renowned Tangut scholar Y.I. Kichanov, "The History of the Tangut State" (1968). The research examines specific provisions from the Tangut legal code, the "Laws Written in Iron of the Heavenly Prosperity Era," particularly concerning land ownership structures, the inheritance system of agricultural land (where priority was given to male children under the age of 14), water resource distribution, and the ninefold fine for livestock theft (the "ninefold penalty"). The article demonstrates that the Tangut state had a well-developed legal framework that efficiently governed its mixed economy, consisting of settled agriculture and nomadic livestock farming.